2018
DOI: 10.3892/etm.2018.6646
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated caveolin‑1 expression serves a potential role in coronary artery spasm by inducing nitric oxide production in�vitro

Abstract: The present study aimed to investigate the effects of downregulated caveolin-1 (Cav-1) expression on nitric oxide (NO) production in lipopolysaccharide (LPS)-damaged primary human umbilical vein endothelial cells (HUVECs) in a model of coronary artery spasm (CAS) microenvironment induced by acetylcholine (ACh) treatment. Small interfering RNA (siRNA)-mediated Cav-1 downregulation in HUVECs was confirmed by western blotting. The cell viability and superoxide dismutase (SOD) inhibition in HUVECs incubated with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Increased expression of Cav1 is known to appear in patients with insulin resistance and type 2 diabetes (54), associated with impaired acetylcholine-induced NO production and vasodilation (55). Cav1 knockout mice show chronic and dramatic elevation in systemic NO levels and enhanced acetylcholine-induced arterial relaxation (56, 57). Conversely, the Bendhack group (58) reported that caveolae disassembled by methyl-β-cyclodextrin (mβcd) treatment cause an impaired acetylcholine-induced relaxation in the rat isolated aorta.…”
Section: Vascular Endothelial Caveolaementioning
confidence: 99%
“…Increased expression of Cav1 is known to appear in patients with insulin resistance and type 2 diabetes (54), associated with impaired acetylcholine-induced NO production and vasodilation (55). Cav1 knockout mice show chronic and dramatic elevation in systemic NO levels and enhanced acetylcholine-induced arterial relaxation (56, 57). Conversely, the Bendhack group (58) reported that caveolae disassembled by methyl-β-cyclodextrin (mβcd) treatment cause an impaired acetylcholine-induced relaxation in the rat isolated aorta.…”
Section: Vascular Endothelial Caveolaementioning
confidence: 99%